Convenient Synthesis and Coordination Properties of p-tert-butyldihomooxacalix[4]Arene Mono-Schiff Bases. (26th May 2020) - Liu, Yang; Zhao, Ling-Ling; Sun, Jing; Yan, Chao-Guo
GRAPHICAL ABSTRACT: ABSTRACT: A series of novel functionalized p - tert -butyldihomooxacalix[4]arene mono-Schiff bases were conveniently synthesized by two-step reaction process. The synthetic rout included alkylation of p - tert -butyldihomooxacalix[4]arene with O -chloroalkoxy-substituted benzaldehydes and sequential condensation with 2-hydroxybenzohydrazide, 2-picolinohydrazideand aminothiourea. The single crystal structures of two p - tert -butyldihomooxacalix[4]arenederivatives were determined by X-ray single crystal diffraction method. The coordination abilities of dihomooxacalix[4]arene mono-Schiff bases towards transition metal ions were preliminarily investigated by UV-Vis spectra.